Umi Fatiha farmers daughter wins Royal Academic Award (Medal of Excellence) - UMP, PNC (2019)
Umi Fatiha Md Kosnin@Md (mailto:Kosnin@Md) Seropil, born in Sungai Balang, Muar, Johor, is the recipient of the Royal Academy Award (Medal of Excellence) at the 14th Universiti Malaysia Pahang (UMP) Convocation Ceremony.